Impact of digital transformation of the economy on economic security - Reshetov, Serhii; Polusmiak, Yuliia (Management and Entrepreneurship: Trends of Development, 2022)
Solving the issues of guaranteeing economic security within the modern realities of digitalization of socio-economic processes is an important and urgent task for the national economy. One of the key tasks of ensuring economic security, which has been actualized in the conditions of non-stationary processes in the modern world, is the task of predicting threats and challenges. The key global challenge to society is digital transformation in almost all specters of modern life. The digitalization of the technosphere plays a significant role in the scientific, social and economic world order, which is seen in the example of the United States, China, Japan - the world’s leading digital powers of our time, since a significant share of the income of their national economies is largely provided by digital technologies. This research is devoted to the study of the economic digitalization impact on economic security, which studies the pros and cons of digitalization, the requirements of the new era of economic security, the experience of digitalization in developed countries. JEL Classification: H56, О10, О40.